(untitled) (Dristikon: A Multidisciplinary Journal, 2020)
This article has attempted to find how the short stories in Rajab‘s collection entitled Paai [Pie] have depicted the realities in the Diaspora through the presentation of characters. Three stories have been selected from the collection. These short fictions are studied in the light of the theory of characterization in short stories. The analysis concentrates on the diasporic identity related cultural, emotional and existential conditions of the characters. The study has found that all the diasporic characters have undergone different types of problems as per their diverse life situations. Generally, all diasporans have identity crisis related to culture. This crisis is connected with their emotion and existence, too. I have also found that there are three types of main characters: general diasporas, senior citizens and young couples. The general diasporans have been used to show the existential conditions of any diasporan in the host land. The depiction of the senior citizens shows how a new land cannot be a good place for them: Most of them are emotionally shocked and unsettled. Even the young couples who reach the USA using all possible means finally feel frustrated and disoriented. Almost all the characters in these stories are unhappy diasporans. It is hoped that this article will encourage researchers to study other diasporic fictions from the point of view of characterization.